Ideal Model Law Analysis Duties and Authorities of Technical Implementation Officials for Activities in the Implementation of Procurement of Goods and Services - Setyo Utomo; Fenty U Puluhulawa; Dian E. Ismail (PT FORMOSA CENDEKIA GLOBAL, 2023)
Now, the duties and authorities of PPTK who are responsible as financial managers by carrying out the duties of Commitment Making Officers are hereinafter abbreviated as PPK as procurement actors. This collaboration of authority between regional financial management and procurement actors will only have a negative impact on bureaucratic structuring to potentially open opportunities for fraud that leads to corruption in the procurement of local government goods/services. The purpose of this study was to answer how the regulatory model for the duties and authorities of Technical Implementation Officers Activities in the implementation of procurement of goods and services. This type of research is a normative juridical with a statutory approach. The results showed that the ideal regulatory model is to maintain each task in the scope of PPTK as an administration of activity management and PPK as a work manager